2019
DOI: 10.1590/1806-9061-2019-1013
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Animal Fat by Canola Oil in Chicken Meatball

Abstract: This work aimed to develop chicken meatballs with five levels of animal fat replacement by canola oil and to evaluate the product's behavior during 120 days of storage. For that, analyzes were performed in the centesimal composition, fatty acid profile, shelf life and sensory parameters. The centesimal composition of the product did not present significant difference (p>0.05) between the treatments. However, canola oil addition improved the lipid profile, atherogenic and thrombogenic indexes, and the ratios of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In addition to their composition, there are few studies that used soybean oil as fat replacers in meat products [ 44 , 45 , 46 ], which demonstrated its viability as animal fat replacer. Finally, canola oil presents high monounsaturated (mainly oleic acid; 60%) and polyunsaturated fatty acids amounts (36%), with intermediate α-linolenic acid contents (about 10%) [ 47 ]. This oil was previously used in the reformulation of chicken meatballs [ 47 ] and sausages [ 48 ], and the results demonstrated a significant nutritional improvement without affecting the sensory characteristics of the products (presented the same consumer acceptability as control samples).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their composition, there are few studies that used soybean oil as fat replacers in meat products [ 44 , 45 , 46 ], which demonstrated its viability as animal fat replacer. Finally, canola oil presents high monounsaturated (mainly oleic acid; 60%) and polyunsaturated fatty acids amounts (36%), with intermediate α-linolenic acid contents (about 10%) [ 47 ]. This oil was previously used in the reformulation of chicken meatballs [ 47 ] and sausages [ 48 ], and the results demonstrated a significant nutritional improvement without affecting the sensory characteristics of the products (presented the same consumer acceptability as control samples).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, canola oil presents high monounsaturated (mainly oleic acid; 60%) and polyunsaturated fatty acids amounts (36%), with intermediate α-linolenic acid contents (about 10%) [ 47 ]. This oil was previously used in the reformulation of chicken meatballs [ 47 ] and sausages [ 48 ], and the results demonstrated a significant nutritional improvement without affecting the sensory characteristics of the products (presented the same consumer acceptability as control samples). Based on these aspects, the use of olive, canola, and soybean oils was proposed in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Direct oil fortification in meat products showed significant drawbacks due to more susceptibility to oxidation reactions, reduced solubility, and increased hardness issues resulting from small fat globules formation (Zetzl et al., 2012). Recently, vegetable oils have been added directly to meat products such as chicken batters (Wirkowska‐Wojdyła et al., 2021), meatballs (Vieira et al., 2019; Öztürk & Turhan, 2020), burgers (Lu et al., 2017; Paula et al., 2019; Antonini et al., 2020), restructured ham‐like products (Ding et al., 2018), fermented Sausages (Bolumar et al., 2015), and chicken nuggets (Barros et al., 2019). These strategies improved fatty acid profile; however, these strategies affect some quality attributes (i.e., flavor, color, and sensory acceptance) of the reformulated products.…”
Section: Methods To Incorporate Plant‐based Oils In Processed Meat Pr...mentioning
confidence: 99%
“…Although the results showed potential, further work was required to match the traditional sausage's texture and sensory attributes. Vieira et al (2019) indicated the substitution of animal fat with canola oil emulsion (citric acid as the antioxidant) as a promising approach to enhance the PUFA/SFA ratio while decreasing the ω-6/ω-3 ratio of chicken meatballs without affecting the texture, color parameters, oxidation, and sensory attributes. In the production of emulsion-type sausages, the use of canola oil in animal fat substitution reduced the SFA content (from 30.38% to 17.41%), increased MUFA (from 41.42% to 52.72%) and PUFA levels (from 26.78% to 27.28%), and decreased the ω-6/ω-3 (from 12.63 to 3.74) ratio.…”
Section: Modification Of Traditional Processed Meat Productsmentioning
confidence: 99%
“…The increase in the world population has driven the demand for improving the quality, quantity, and diversity of oil sources (Prates-Valério, Celayeta & Cren, 2019). This led to the popularization of the consumption of vegetable oils associated with the search and development of new sources (Senger et al, 2017) aiming its beneficial effects on human health and high consumer acceptance (Vieira, Souza, Rodrigues & Sousa, 2019). In this context, studies with bioactive lipids from easily available plant sources have been conducted in order to analyse their quality, stability, and nutritional characteristics (Hashempour-baltork, Torbati, Azadmard-damirchi & Savage, 2016;Ramadan & Wahdan, 2012).…”
Section: Introductionmentioning
confidence: 99%